Online three-tier diagnostic test to identify misconception about virus and COVID-19 - Refsya Aulia Fikri; Hadi Suwono; Herawati Susilo (JPBI (Jurnal Pendidikan Biologi Indonesia), 2022)
During the COVID-19 pandemic, various misinformation circulating among the public has the potential to be a source of misconceptions.  This study aimed to validate the online three-tier diagnostic instrument test for Virus and COVID-19 as well as analyze the level of misconceptions experienced by students. The Treagust model is used as a reference for the instrument development process.  Three public high schools providing 187 second grade students who had previously studied Virus content were involved as research respondents, The data analysis techniques used were descriptive statistics. Construct and content validity obtained from expert validation reached 89.88% and 97.12%, respectively.  The results of data analysis also inform that each item was valid and the instrument was reliable.  The average percentage of students who experience misconceptions was 39.96%. The average percentage of students who understand the topic correctly was 32.10%. The percentage of lucky guess reached 14.83% and students with low level of knowledge reached 13.10%. The diagnostic test as overall, was successful in detecting students’ misconceptions.  To overcome misconceptions and improve the quality of learning during a pandemic, biology learning must apply creative learning models, methodologies, and teaching materials.